General insights on obstacles to dog vaccination in Chad on community and institutional level - Mbaipago, Nodjimbadem; Madjadinan, Alladoumngar; Amalaman, Djedou Martin; Andrée Ndour, Prisca; Zinsstag, Jakob; Heitz-Tokpa, Kathrin; Lechenne, Monique (Frontiers in Veterinary Science, 2022)
Domestic dogs are responsible for 95% of all human rabies cases worldwide and continue to be the main reservoir for this fatal virus in African and Asian countries. Interrupting the spread of the disease in the domestic dog population is therefore necessary for long-term, sustainable rabies control. In Chad is endemic, but no national control strategy is in place to date and dog vaccination coverage is very low. This qualitative, descriptive study aims to identify the main barriers to dog vaccination on both the community and the institutional level from a socio-anthropological point of view in Chad. The study was embedded in an overall project conducted from 2016-2018, to determine rabies burden and vaccine demand in West and Central Africa. Data collection was conducted on the occasion of the project’s closing workshops with stakeholders organized between August to September 2018. We conducted interviews and focus group discussions (FGD) among veterinary officers and dog owners. Participants were selected purposively based on their place of work or residence and their previous contact with the project. In addition, interviews were conducted with community leaders and veterinary officials. Economic constraints encountered relate to the cost of the vaccine itself and the expenses for transporting the dogs to the vaccination site. The cultural belief that the vaccine will have an impact on the therapeutic properties of dog meat for consumers (observed in Southern Chad), and the fact that dogs are considered impure animals in Muslim faith, which prohibits handling of dogs, are obstacles identified on the sociocultural level. At the institutional level, the unavailability of vaccines in veterinary services, the lack of communication about the law on dog vaccination, the absence of rabies in the training curricula of veterinary agents, and the lack of intersectoral collaboration limit vaccination coverage. Although our study design did not allow a detailed analysis of obstacles related to socio-economic level, gender and age the broad insights gained can provide general guidance for future interventions in Chad and similar countries on the way to zero human deaths due to rabies by 2030.